Development of a novel testis-on-a-chip that demonstrates reciprocal crosstalk between Sertoli and Leydig cells in testicular tissue - Se-Ra Park; Myung Geun Kook; Soo-Rim Kim; Choon-Mi Lee; Jin Woo Lee; Jung-Kyu Park; Chan Hum Park; Byung-Chul Oh; YunJae Jung; In-Sun Hong (Experimental and Molecular Medicine, 2024)
Abstract The reciprocal crosstalk between testicular Sertoli and Leydig cells plays a vital role in supporting germ cell development and maintaining testicular characteristics and spermatogenesis. Conventional 2D and the recent 3D assay systems fail to accurately replicate the dynamic interactions between these essential endocrine cells. Furthermore, most in vitro testicular tissue models lack the ability to capture the complex multicellular nature of the testis. To address these limitations, we developed a 3D multicellular testis-on-a-chip platform that effectively demonstrates the reciprocal crosstalk between Sertoli cells and the adjacent Leydig cells while incorporating various human testicular tissue constituent cells and various natural polymers infused with blood coagulation factors. Additionally, we identified SERPINB2 as a biomarker of male reproductive toxicity that is activated in both Sertoli and Leydig cells upon exposure to various toxicants. Leveraging this finding, we designed a fluorescent reporter-conjugated toxic biomarker detection system that enables both an intuitive and quantitative assessment of material toxicity by measuring the converted fluorescence intensity. By integrating this fluorescent reporter system into the Sertoli and Leydig cells within our 3D multicellular chip platform, we successfully developed a testis-on-chip model that can be utilized to evaluate the male reproductive toxicity of potential drug candidates. This innovative approach holds promise for advancing toxicity screening and reproductive research.